2017
DOI: 10.1089/dna.2017.3668
|View full text |Cite
|
Sign up to set email alerts
|

The Type I Interferon Response and Age-Dependent Susceptibility to Herpes Simplex Virus Infection

Abstract: Herpes simplex virus type 1 (HSV-1) is a highly prevalent human neurotropic pathogen. HSV-1 infection is associated with a variety of diseases ranging from benign orolabial lesions to more serious and even life-threatening conditions such as herpes simplex keratitis and herpes simplex encephalitis (HSE). HSE is a rare occurrence among healthy adult individuals, but newborns are a particularly susceptible population. Type I IFN signaling has been identified as a crucial component of the innate immune response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…These inconsistent results between studies could be explained by the use of different in vitro models, and could be verified in enteroid models 21 . Interestingly, there is an age‐dependent increase in the ability of monogastrics and ruminants to produce type 1 IFN in response to viral infection, and this difference may also help to explain the increased susceptibility of young children and neonatal cattle to Cryptosporidium infection 101‐103 …”
Section: Defensive Function Of the Intestinal Epithelium Against Crypmentioning
confidence: 99%
“…These inconsistent results between studies could be explained by the use of different in vitro models, and could be verified in enteroid models 21 . Interestingly, there is an age‐dependent increase in the ability of monogastrics and ruminants to produce type 1 IFN in response to viral infection, and this difference may also help to explain the increased susceptibility of young children and neonatal cattle to Cryptosporidium infection 101‐103 …”
Section: Defensive Function Of the Intestinal Epithelium Against Crypmentioning
confidence: 99%
“…Mice display an age-dependent acceleration of mortality due to influenza virus (IAV) infection, and are useful for modeling human aging and the outcomes of IAV infection [ 13 ]. It has been suggested that the maturation of the innate immune system and the expression of type I interferon genes may contribute to age-related viral susceptibility [ 14 ]; however, the reason for the differential gene expression patterns between young and adult patients is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This is in stark contrast to adult HSV-1 infections, which are largely asymptomatic or result in benign mucocutaneous disease. Several studies have aimed at studying age-dependent differences in the immune response to HSV-1 between newborns and adults (17,(38)(39)(40)(41)(42)(43), but our understanding of the significant difference in disease outcomes in this population remains limited. Several promising candidates for an effective HSV vaccine have failed to show efficacy in clinical trials (44,45).…”
Section: Discussionmentioning
confidence: 99%